Implementasi Nilai-Nilai Pancasila dalam Pembentukan Karakter Mahasiswa Universitas Negeri Surabaya - Surya Putri , Amara Dwi; Cantika Parama Putri, Evelyn; Dwi Rahmawati, Salsya Putri; Ika Puspita, Ari Metalin (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The development of character which is marked by changing times has led to awareness towards the decline in the application of Pancasila values as students in everyday life. This research aims to assess how important it is to implement Pancasila values in daily life. This research is aimed at students at Surabaya State University. Observation results show that students are active in playing out the 5 values of Pancasila through daily activities in social, religious, deliberative and just life. However, there are obstacles due to the progress of the times which makes the author observe the development of the character of Pancasila values in Surabaya State University students.